2017
DOI: 10.24289/ijsser.270771
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen adaylarının matematik öğretiminde oyunların kullanımı ile ilgili görüşleri

Abstract: Öğretmen adaylarının matematik öğretiminde oyunların kullanımı ile ilgili görüşleri 1,2The opinions of pre-service teachers on the usage of games in mathematics teaching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 3 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In the study conducted by Uğurel (2003), it was seen that teachers and teacher candidates stated that teaching with games increase the interest of students in math, develop their problem-solving skills, make students active during the classes, make them build healthy communication, increase motivation, and provide an opportunity for information to be permanent and fast-learned. In the studies conducted by Hoşgör (2010), Güneş (2010) and Usta et al (2016), teachers and teacher candidates stated that using games in teaching math enables a clearer understanding of the topics, a permanent learning, stimulates students in the positive way, and enables their socialization, and contributes to the mental development of students. At the same time, it was also seen that the students developed positive attitude towards math, focused on the class, and actively participated.…”
Section: Result Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Uğurel (2003), it was seen that teachers and teacher candidates stated that teaching with games increase the interest of students in math, develop their problem-solving skills, make students active during the classes, make them build healthy communication, increase motivation, and provide an opportunity for information to be permanent and fast-learned. In the studies conducted by Hoşgör (2010), Güneş (2010) and Usta et al (2016), teachers and teacher candidates stated that using games in teaching math enables a clearer understanding of the topics, a permanent learning, stimulates students in the positive way, and enables their socialization, and contributes to the mental development of students. At the same time, it was also seen that the students developed positive attitude towards math, focused on the class, and actively participated.…”
Section: Result Discussion and Recommendationsmentioning
confidence: 99%
“…In these studies, teaching with gamification method has an impact on the academic success of students (Kebritchi et al, 2008;Ashirbayev et al, 2015;Boz, 2018;Galiç, 2020;Denli, 2021), an effect on the acquisition of process skills (Kılıç, 2010), on the access and permanency of students (Demir, 2016), teaching mathematics with gamification and its effect on the access, attitude and motivations of students (Tural, 2005;Biriktir, 2008;Galiç, 2020), the mathematical sufficiency of students (Chang, 2015) and strengthens their problem solving skills (Yılmaz, 2019a) are encountered. In addition, in the studies carried out by Uğurel (2003), Hoşgör (2010), Güneş (2010) and Usta et al (2016), teacher opinions regarding the teaching with gamification methods were examined. In these studies, there is no research determining the levels of the use of games in teaching by the teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Özyürek and Çavuş (2016) determined that primary school teachers use the game method in lessons and have the opinion that the game method ensures permanent learning and increases the rate of the active participation of students in lessons. In the study of Usta et al (2017), the opinions of preservice teachers were taken, and they were asked about their opinions on teaching mathematics with games, difficulties they face when preparing games, and whether they would use the games in mathematics lessons when they become teachers. As a result, it was found that preservice teachers thought that using games in mathematics lessons is necessary and beneficial, the fear of the mathematics lesson could be reduced in an entertaining learning environment, and thus, it would make mathematics lesson more concrete and understandable.…”
Section: Discussionmentioning
confidence: 99%